EFEKTIVITAS METODE KWL (KNOW, WANT TO KNOW, LEARNED) TERHADAP PEMAHAMAN MEMBACA TEKS NONFIKSI SISWA KELAS V SD MUHAMMADIYAH KARUWISI KOTA MAKASSAR - Nur Indah Sari, Hesti; Adam, Andi; Ayu Andhira, Desy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The main problem in this study is the lack of reading comprehension among fifth-grade students of SD Muhammadiyah Karuwisi, Makassar. Therefore, the researcher applied the KWL (Know, Want to Know, Learned) method, which is expected to encourage students to better understand the content of reading texts. This study aims to determine the effectiveness of the KWL (Know, Want to Know, Learned) method on the reading comprehension of fifth-grade students at SD Muhammadiyah Karuwisi, Makassar. This study employed a quantitative experimental method with a One Group Pre-test and Post-test Design. The population of this study consisted of all fifth-grade students of SD Muhammadiyah Karuwisi, totaling 10 students. The sampling technique used was total sampling, meaning that the entire population was used as the research sample. The data collection techniques were conducted through a pre-test and post-test. The data were collected using a reading comprehension competency test in the form of constructed-response items. Afterward, all obtained data were analyzed using descriptive statistics and inferential statistics. Based on the results, the average pre-test score was 58.50, categorized as low, and the average post-test score was 83.00, categorized as high. Furthermore, the results of the inferential analysis through hypothesis testing using the Paired Samples Test showed a Sig. (2-tailed) value of 0.000. Thus, H0 was rejected and H1 was accepted because the Sig. (2-tailed) value < α (0.05), namely (0.000 < 0.05). Therefore, it can be concluded that the KWL (Know, Want to Know, Learned) method is effective in improving the reading comprehension of nonfiction texts among fifth-grade students of SD Muhammadiyah Karuwisi, Makassar.